Ultra-fast growth of cuprate superconducting films: Dual-phase liquid assisted epitaxy and strong flux pinning. (May 2021) - Wu, Yue; Zhao, Yue; Han, Xiaocang; Jiang, Guangyu; Shi, Jiangtao; Liu, Pan; Khan, Mukarram Zaman; Huhtinen, Hannu; Zhu, Jiamin; Jin, Zhijian; Yamada, Yutaka
Abstract: Cuprate superconductors are key candidate materials toward high energy-efficient devices. Improving their growth rate and performance under magnetic fields are indispensable for achieving even higher efficiency. For the first time, we demonstrated the ultra-high rate up to 100 nm/s in the growth of dual-phase cuprate superconducting film (EuBa2 Cu3 O7 -BaHfO3 ). The growth rate achieved is two orders of magnitude higher than that at lab-scale and was also the highest on record to our best knowledge. Epitaxial growth mechanism assisted by the transient liquid phase is proposed, as evidenced by formation of Eu2 BaCuO5 and Ba–Cu–O metastable phases under high supersaturation conditions. The high growth rate results in formation of mixed defective landscape, consisting of short nanorods, nanoparticles and naturally formed defects (e.g., staking faults). Due to such unique microstructure, we confirm that weak J c anisotropy is dominated by random pinning mechanism. Contribution of isotropic and anisotropic J c to J c total also varies with temperatures and magnetic field strength, which is a consequence of evolution of dominant pinning in film. As a result, the in-field current carrying capacity is significantly enhanced (exceeding 430 A/4 mm-width at 4.2 K, 18 T, B // c ), being among the top tier of commercialized superconductor materials. This study establishes the correlation between ultra-high growth rate and flux pinning behaviors, which provides feasibility of dramatically improvement of production efficiency with the low price-performance ratio of future high temperature superconductor. Graphical abstract: Image 1 Highlights: An advanced pulsed laser deposition technique with the ultra-high growth rate. A growth mechanism assisted by the transient liquid phase in complex oxide films. The mixture pinning landscape of BHO nano-particles and stacking faults. Weak anisotropy and strong pinning induced by random pinning mechanism. Enhanced in-field current carrying capacity at low temperature.